The Effectiveness of Tax Policy in Encouraging Domestic Investment in Indonesia - Franciska, Laudya (Utami Publisher, 2025)
This study focuses on analyzing the effectiveness of tax policies in stimulating domestic investment growth in Indonesia. The government has actively introduced various fiscal incentive instruments, including tax holidays, tax allowances, and reductions in corporate income tax rates, as strategies to improve the investment climate and attract domestic entrepreneurs. However, the implementation of these policies has not fully achieved optimal outcomes. This is due to several structural obstacles, such as complex bureaucratic procedures, regulatory uncertainty that confuses investors, and limited tax literacy among local business actors. This research adopts a qualitative approach with descriptive methods, utilizing secondary data sourced from fiscal policy reports, financial institution publications, and relevant academic documentation. The analysis reveals that although fiscal incentives positively impact domestic investment interest, their realization is still hindered by weak inter-agency coordination, lack of transparency, and limited technical support. Therefore, a more comprehensive reform is needed, including simplification of regulatory systems, digitalization of business licensing services, and improvement of tax literacy through integrated training programs. Furthermore, strengthening the capacity of fiscal institutions and ensuring legal certainty are crucial factors in enhancing investor confidence and reinforcing the contribution of domestic investment to national economic growth.